Keys to Becoming a Great Lecturer: Motivation, Competency, and Discipline - Erwin Setiawan (Jurnal Informatika Ekonomi Bisnis, 2025)
This study explores how motivation, competency, and work discipline interact to influence lecturer performance at STP Bandung. Using a quantitative approach, data were collected via structured surveys of full-time lecturers. Path analysis revealed that motivation enhances engagement, competency ensures expertise, and work discipline maintains consistency, together accounting for about 80% of the variance in lecturer performance. These findings highlight the importance of a comprehensive lecturer development strategy that integrates recognition-driven motivation, ongoing professional development, and balanced disciplinary frameworks. Practical recommendations include implementing performance-based incentives, establishing structured training programs, promoting participatory governance, and adopting adaptive technologies. Collectively, these initiatives aim to cultivate lecturers who are empowered, skilled, and fully engaged in advancing academic excellence.